White Paper of the Society of Computed Body Tomography and Magnetic Resonance on Dual-Energy CT, Part 4: Abdominal and Pelvic Applications. Issue 1 (January 2017) - De Cecco, Carlo N.; Boll, Daniel T.; Bolus, David N.; Foley, W. Dennis; Kaza, Ravi K.; Morgan, Desiree E.; Rofsky, Neil M.; Sahani, Dushyant V.; Schoepf, U. Joseph; Shuman, William P.; Siegel, Marilyn J.; Vrtiska, Terri J.; et al.
Abstract : Abstract: This is the fourth of a series of 4 white papers that represent expert consensus documents developed by the Society of Computed Body Tomography and Magnetic Resonance through its task force on dual-energy computed tomography. This article, part 4, discusses DECT for abdominal and pelvic applications and, at the end of each, will offer our consensus opinions on the current clinical utility of the application and opportunities for further research.